Blockchain technology in the healthcare industry: trends and opportunities - Hussien, Hassan Mansur; Md Yasin, Sharifah; Udzir, Nur Izura; Ninggal, Mohd Izuan Hafez; Salman, Sadeq (Elsevier, 2021)
The growth in the use of blockchain technology in healthcare is remarkable and has a significant impact on the healthcare industry. In this work, the gap between the healthcare industry and blockchain technologies was addressed by evaluating previous activities. Bibliometric analysis of dataset distribution, venues, keywords and citations was conducted to identify the trend of blockchain technology in healthcare. Case studies of telecare medicine information system and E-health were also reviewed and evaluated in terms of security and privacy. This study discussed potential future challenges such as scalability and storage capacity, blockchain size, universal interoperability and standardisation. This work highlighted the motivations of employing blockchain technology in the healthcare industry. Prospects in health data and sharing process, clinical trials, the pharmaceutical industry, big data, artificial intelligence, 5 G ultrasonic device, security and privacy were highlighted.